The Treatment of Hexavalent Chromium Induced Ovarian Cancer in Albino Rats with Emblica Officinalis. A Comparative Study - Naveed Shuja, Nabeela Zeeshan, Shahnaz Bano Memon, Asad Ali Zardari, Bakhtawar Mateen, Alina Saqib, Ihsan Ullah Khan, Arslan Shuja, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Ovarian cancer may be treated with medicinal herbs like extract from Emblica officinalis Phytochemicals of this herb have antioxidant efficacy against oxidants and reduce cellular as well as genotoxicity. Aims and objectives: In current study hexavalent chromium induced ovarian cancer in albino rats were treated with emblica officinalis extract through a piolet project and measured its efficacy with the passage of time. Research Design: A comparative study of medicinal herbs, Emblica officinalis against ovarian cancer. Population Sampling: In this study female albino rates of about 100 gram body weight were selected comparatively. Sample Size: 15 female albino rates about equal weight were selected and divided them into different groups. Place and Duration: Present study was conducted from January 2022 to June 2022 at animal house of IMBB the University of Lahore and Biochemistry Department of Lahore Medical & Dental College Lahore Pakistan. Methodology: Total 15 female albino rates were selected in this study and divided them into different groups. In Group-A which is control all individuals were normal and not treated with anything. In Group-B and Group-C there were 5 rates in each group and they were treated with different strength of Emblica officinalis extract in distil water. Results: It has seen that the blood serum levels of CA-125, Alpha-fetoprotein and Lactate dehydrogenase in both group-B and group-C presented in table-2, table-3, table-4 and table-5 showed a remarkable significant changes (P≤0.05) after intervals of time. The significant changes in blood serum levels of CA-125, Alpha-fetoprotein and Lactate dehydrogenase (37±0.01, 42±0.01, 341±0.01) were noted in group-C individuals how were treated with 10mg/body weight ethanolic extract of Emblica officinalis for two month as compared to the control group-A. Practical implication Conclusion: The significant changes in blood serum levels of CA-125, Alpha-fetoprotein and Lactate dehydrogenase (37±0.01, 42±0.01, 341±0.01) were noted in group-C individuals how were treated with 10mg/body weight ethanolic extract of Emblica officinalis for two month as compared to the control group-A. Keywords: Alpha-fetoprotein, Lactate dehydrogenase, Emblica officinalis, Hexavalent Chromium